The Influence Of Price Perceptions and Promotional Strategies In Social Media On The Decision To Use Asa Photography Ser vices In The City Of Tasikmalaya (Survey On Consumers Of Asa Photography Photo Services In The City Of Tasikmalaya) - Putri, Amelia; Pauzy, Depy Muhamad; Karmila, Mila (Universitas Dehasen Bengkulu, 2023)
The purpose of this study is to determine the effect of price perception and promotional strategies on social media on the decision to use ASA photography services in Tasikmalaya City. The research method used is a quantitative method with a survey approach to 100 respondents who are consumers of ASA Photography. The types of data used are primary data and secondary data. The data analysis technique used is multiple regression analysis. The results of this test prove that price perceptions and promotion strategies on social media have a significant effect both partially and simultaneously on the consumer's decision to use ASA photography in the city of Tasikmalaya.